Analisis Kerugian Ekonomi serta Pengetahuan Masyarakat terhadap Konflik Orangutan Sumatera (Pongo abelii) - Oni Sri Rahayu Sitorus; Pindi Patana; Agus Purwoko (Peronema Forestry Science Journal, 2014)
Research on “Analysis of Economic Loss and Society Knowledge of Orangutan Sumatra (Pongo abelii) conflict” was conducted in March 2013 until April 2013 at Kuta Gajah and Besilam Village by interview inhabitants whose land damage by the orangutan. The purpose of this research are to calculate the total economic loss caused by the conflicts, to know the cost of community, NGO and government have been spend for mitigating conflict between human and Orangutan Sumatera (P. abelii) and also to analyze community knowledge about the reasons of the conflicts. The result of this research showed that total economic loss at Kuta Gajah is higher than Besilam. Total economics loss occured to Kuta Gajah villager was Rp 2.120.952,00, that clasified to high, while occured to Besilam villager was Rp 340.,00 and clasified to low.  In conflict mitigation, governments cooperated with OIC and by evacuating into Gunung Leuser National Park Area.Keywords: Orangutan Sumatra, Orangutan conflict, Economic Loss, Mitigation Cost, Gunung Leuser National Park.